Solid electrolyte high-entropy ceramic with high conductivity and preparation method thereof
By introducing five elements into oxygen ion solid electrolyte ceramic materials and adopting a high entropy design, the problems of low conductivity and poor stability at medium and low temperatures are solved, and high conductivity and long-term stability of ceramic materials are achieved.
Patent Information
- Application Number
- CN202510022621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing oxygen ion solid electrolyte ceramic materials have low conductivity at medium and low temperatures, and there are problems of phase transformation and crystal form transformation, and their long-term operation stability is poor.
Using a high entropy design strategy, the configuration entropy and lattice distortion are improved by introducing five elements of equal molar ratios (Er, Dy, Gd, Zr and Y) into the sample fluorite lattice, thereby increasing the lattice stability and oxygen ion conductivity.
The oxygen ion conductivity is significantly improved, one to two orders of magnitude is increased, and the phase structure remains stable after long-term insulation at medium and low temperatures, and no other phases are generated.
Smart Images

Figure CN119797916A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a solid electrolyte high-entropy ceramic with high electrical conductivity and a preparation method thereof. Background Art
[0002] So far, the commonly used oxygen ion solid electrolyte ceramics that have been developed and studied mainly include zirconium oxide-based, cerium oxide-based, lanthanum gallate-based and bismuth oxide-based oxygen ion solid electrolytes, etc. Among them, the conductivity of the first three electrolytes is relatively low, while the bismuth oxide-based oxygen ion solid electrolyte ceramics with defective fluorite-type structure have higher oxygen ion conductivity, which is mainly attributed to the 25% intrinsic oxygen defects in its lattice. However, pure Bi2O3 has different crystal structures at different temperatures. The stable temperature range of fluorite-type Bi2O3 (δ-Bi2O3) with higher oxygen ion conductivity is 730℃~825℃. When the temperature is lower than 730℃ or higher than 825℃, Bi2O3 will undergo phase change or transform into a molten state. In order to enable Bi2O3 to maintain a stable δ-Bi2O3 phase in the range from room temperature to the operating temperature of O-SOFC, element doping is usually used to broaden the temperature range of its crystal stability.
[0003] Although the traditional single-element doping or two-element co-doping method prevents the phase transformation of δ-Bi2O3-based electrolytes at low temperatures, its conductivity at medium and low temperatures still needs to be further improved. At the same time, single-element doping or multi-element doping δ-Bi2O3-based electrolytes still have the problem of poor long-term operating stability. In medium and low temperature environments, their oxygen ion conductivity will gradually decay with the increase of time and finally tend to stabilize. This is mainly related to the disorder-order transformation of anion sublattices in the crystal structure of δ-Bi2O3-based electrolytes. At present, there has been no research or report on the high-entropy design of δ-Bi2O3-based electrolyte ceramic materials. The so-called high-entropy ceramics generally refer to multi-principal solid solution ceramics composed of five or more elements in equal or near molar ratios. According to relevant reports on high-entropy ceramic materials, with the help of the high mixing entropy and hysteresis diffusion effect of high-entropy materials, the thermal stability of δ-Bi2O3-based electrolyte ceramic materials can be improved, the occurrence of phase transformation can be inhibited, and its performance can be further improved.
[0004] In view of the low conductivity of existing oxygen ion conductors and the phase change and crystal transformation of bismuth oxide, the present invention adopts a high entropy design strategy to provide a high conductivity (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) x Bi 1-x )2O3 oxygen ion solid electrolyte high entropy ceramics. Summary of the invention
[0005] Based on this, the present invention provides a solid electrolyte high entropy ceramic with high conductivity and a preparation method thereof. The present invention introduces five elements (Er, Dy, Gd, Zr and Y) in equal molar ratios into the sample fluorite-type lattice to increase the configuration entropy and lattice distortion of the sample, thereby increasing the lattice stability and oxygen ion conductivity of the sample.
[0006] Specifically, the present invention is implemented by adopting the following technical solutions:
[0007] A solid electrolyte high entropy ceramic with high electrical conductivity, characterized in that the structure of the solid electrolyte high entropy ceramic is as follows:
[0008] (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) x Bi 1-x )2O3,
[0009] Where x=0.1~0.2.
[0010] Preferably, the solid electrolyte high entropy ceramic of the present invention has a cubic fluorite crystal structure and is composed of irregular polygonal grains.
[0011] The method for preparing a solid electrolyte high entropy ceramic with high electrical conductivity of the present invention comprises the following steps:
[0012] (1) Weighing Er2O3 powder, Dy2O3 powder, Gd2O3 powder, ZrO2 powder, Y2O3 powder and Bi2O3 powder in stoichiometric ratios respectively, and then ball-milling the weighed oxide powders to obtain a mixed powder;
[0013] (2) calcining the mixed powder in a muffle furnace, and grinding and sieving the mixed powder after calcination to obtain a precursor powder;
[0014] (3) Pressing the precursor powder into a disc, placing the disc in a crucible, laying the precursor powder on the bottom of the crucible, and then sintering the crucible in a muffle furnace to obtain a solid electrolyte high entropy ceramic.
[0015] Preferably, the ball milling medium in step (1) of the present invention is zirconium oxide grinding balls and anhydrous ethanol, wherein the mass ratio of the raw material powder to the zirconium oxide grinding balls and anhydrous ethanol is 1:(5-6):(5-6), the ball mill speed is 300-350rpm, and the ball milling time is 20-24h. In some embodiments, the present invention fully dries the light yellow slurry after ball milling, and then grinds the light yellow block obtained by drying into fine powder to obtain a mixed powder. The drying temperature is preferably 100-110°C, and the drying time is preferably 10-12h.
[0016] Preferably, the muffle furnace calcination temperature in step (2) is 500-600° C., and the calcination time is 5-6 hours.
[0017] In some embodiments, the present invention forms a round piece with a diameter of 10 mm and a thickness of 1.5 mm at a pressure of 112 to 135 MPa for 5 to 15 minutes.
[0018] Preferably, in step (3), the sintering temperature in the muffle furnace is 800-950° C., and the holding time is 8-10 h.
[0019] Principle of the present invention: Although the traditional single-element doping or two-element co-doping method prevents the phase transition of δ-Bi2O3-based electrolytes at low temperatures, its oxygen ion conductivity at medium and low temperatures (≤500°C) is low. At the same time, single-element doped or co-doped δ-Bi2O3-based electrolytes also have the problem of poor structural stability during long-term operation. The present invention selects five elements with different ion radii and atomic masses and adds them to the sample lattice, which can significantly improve the configurational entropy and lattice distortion of the sample, increase the stability of the sample's fluorite lattice, promote the formation of oxygen vacancies, and improve its oxygen ion conductivity.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) x Bi 1-x )2O3 oxygen ion solid electrolyte high entropy ceramics, after being doped with five specific elements in equal proportions, have a maximum oxygen ion conductivity (4.05×10 -2 S / cm) is one to two orders of magnitude higher than that of traditional oxygen ion solid electrolyte ceramics such as doped Bi2O3-based ceramics, CeO2-based ceramics and yttria-stabilized zirconia ceramics (8.24×10 -4 S / cm~6.29×10 -3 S / cm(500℃)).
[0022] (2) The ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) x Bi 1-x After the 2O3 oxygen ion solid electrolyte high entropy ceramics were kept at 500℃ for a long time (100h), its phase structure remained stable and no other phases were generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of the solid electrolyte high entropy ceramics prepared in Examples 1 to 3 and Comparative Example 1 after sintering;
[0024] Figure 2 XRD patterns of the solid electrolyte high entropy ceramics prepared in Examples 1 to 3 and Comparative Example 1 after annealing at 500° C. for 100 h;
[0025] Figure 3 The SEM and EDS images of the solid electrolyte high entropy ceramics prepared in Examples 1 to 3;
[0026] Figure 4 Arrhenius plot, AC impedance plot and conductivity of the solid electrolyte high entropy ceramics prepared in Examples 1 to 3 and Comparative Example 1 in the range of 200 to 600°C, DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the preferred embodiments of the present invention are further described in detail in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A high conductivity (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9 ) A method for preparing a 2O3 oxygen ion solid electrolyte high entropy ceramic, the specific steps are as follows:
[0030] (1) According to ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi0.9 )2O3 in a stoichiometric ratio of Er2O3, Dy2O3, Gd2O3, ZrO2, Y2O3 and Bi2O3 were weighed respectively, and then the weighed oxide powders were poured into a zirconia ball mill jar, zirconia grinding balls and anhydrous ethanol were added as ball milling media, the mass ratio of raw material powder, zirconia grinding balls and anhydrous ethanol was 1:5:5, and a planetary ball mill was used to mill at a speed of 300 rpm for 24 hours.
[0031] (2) The light yellow slurry obtained in step (1) was poured into a glass dish and placed in a drying oven at 100° C. for 12 h. The dried light yellow block was then ground into fine powder using an agate mortar and poured into an alumina crucible and placed in a muffle furnace for calcination at 500° C. for 6 h to obtain (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9 )2O3 precursor powder.
[0032] (3) The ((Er obtained in step (2) 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9 )2O3 precursor powder was ground in an agate mortar for half an hour and passed through a 300-mesh sieve. Then, a stainless steel mold and a powder tablet press were used to press ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9 )2O3 precursor fine powder was pressed into a disc with a diameter of 10mm and a thickness of 1.5mm, and the pressure was maintained for 5min. Finally, the disc was placed in an alumina crucible, and the bottom of the crucible was covered with ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9 )2O3 precursor powder was placed in a muffle furnace at 800℃ for 10h to obtain ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.1 Bi 0.9)2O3 oxygen ion solid electrolyte high entropy ceramics.
[0033] Example 2
[0034] A high conductivity (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 ) A method for preparing a 2O3 oxygen ion solid electrolyte high entropy ceramic, the specific steps are as follows:
[0035] (1) According to ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 in a stoichiometric ratio of Er2O3, Dy2O3, Gd2O3, ZrO2, Y2O3 and Bi2O3 were weighed respectively, and then the weighed oxide powders were poured into a zirconia ball mill jar, zirconia grinding balls and anhydrous ethanol were added as ball milling media, the mass ratio of raw material powder, zirconia grinding balls and anhydrous ethanol was 1:6:6, and a planetary ball mill was used for ball milling at a speed of 350 rpm for 20 hours.
[0036] (2) The light yellow slurry obtained in step (1) was poured into a glass dish and placed in a drying oven at 110° C. for 10 h. The dried light yellow block was then ground into fine powder using an agate mortar and poured into an alumina crucible and placed in a muffle furnace for calcination at 600° C. for 5 h to obtain (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 precursor powder.
[0037] (3) The ((Er obtained in step (2) 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 precursor powder was ground in an agate mortar for half an hour and passed through a 300-mesh sieve. Then, a stainless steel mold and a powder tablet press were used to press ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y0.2 ) 0.15 Bi 0.85 )2O3 precursor powder was pressed into a disc with a diameter of 10 mm and a thickness of 1.5 mm, and the pressure was maintained for 10 min. Finally, the disc was placed in an alumina crucible, and the bottom of the crucible was covered with ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 precursor powder was placed in a muffle furnace at 900℃ for 10h to obtain ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 oxygen ion solid electrolyte high entropy ceramics.
[0038] Example 3
[0039] A high conductivity (Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 ) A method for preparing a 2O3 oxygen ion solid electrolyte high entropy ceramic, the specific steps are as follows:
[0040] (1) According to ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 in a stoichiometric ratio of Er2O3, Dy2O3, Gd2O3, ZrO2, Y2O3 and Bi2O3 were weighed respectively, and then the weighed oxide powders were poured into a zirconia ball mill, zirconia grinding balls and anhydrous ethanol were added as ball milling media, the mass ratio of raw material powder, zirconia grinding balls and anhydrous ethanol was 1:5:5.5, and a planetary ball mill was used to mill at a speed of 330 rpm for 22 h.
[0041] (2) The light yellow slurry obtained in step (1) was poured into a glass dish and placed in a drying oven at 105° C. for 11 h. The dried light yellow block was then ground into fine powder using an agate mortar and poured into an alumina crucible and placed in a muffle furnace for calcination at 550° C. for 5.5 h to obtain (Er 0.2 Dy 0.2 G0.2 Zr 0.2 Y 0.2 ) 0.15 Bi 0.85 )2O3 precursor powder.
[0042] (3) The ((Er obtained in step (2) 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 precursor powder was ground in an agate mortar for half an hour and passed through a 300-mesh sieve. Then, a stainless steel mold and a powder tablet press were used to press ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 precursor fine powder was pressed into a disc with a diameter of 10mm and a thickness of 1.5mm, and the pressure was maintained for 15min. Finally, the disc was placed in an alumina crucible, and the bottom of the crucible was covered with ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 precursor powder was placed in a muffle furnace at 950℃ for 8h to obtain ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 oxygen ion solid electrolyte high entropy ceramics.
[0043] Comparative Example 1
[0044] A single-doped Bi2O3-based oxygen ion solid electrolyte ceramic (Er 0.2 Bi 0.8 )2O3 preparation method, the specific steps are as follows:
[0045] (1) According to (Er 0.2 Bi 0.8)2O3 in a stoichiometric ratio of Er2O3 and Bi2O3, respectively, and then pour the weighed oxide powders into a zirconia ball mill, add zirconia grinding balls and anhydrous ethanol as ball milling media, the mass ratio of raw material powder, zirconia grinding balls and anhydrous ethanol is 1:5:5.5, use a planetary ball mill at a speed of 330 rpm for 22 hours.
[0046] (2) The light yellow slurry obtained in step (1) was poured into a glass dish and placed in a drying oven at 105° C. for 11 h. The dried light yellow block was then ground into fine powder using an agate mortar and poured into an alumina crucible and placed in a muffle furnace for calcination at 550° C. for 5.5 h to obtain (Er 0.2 Bi 0.8 )2O3 precursor powder.
[0047] (3) The (Er) obtained in step (2) 0.2 Bi 0.8 )2O3 precursor powder was ground in an agate mortar for half an hour and passed through a 300-mesh sieve. Then, a stainless steel mold and a powder tablet press were used to press (Er 0.2 Bi 0.8 )2O3 precursor powder was pressed into a disc with a diameter of 10 mm and a thickness of 1.5 mm, and the pressure was maintained for 15 min. Finally, the disc was placed in an alumina crucible, and the bottom of the crucible was covered with (Er 0.2 Bi 0.8 )2O3 precursor powder was placed in a muffle furnace at 950℃ for 8h to obtain (Er 0.2 Bi 0.8 )2O3 oxygen ion solid electrolyte high entropy ceramics.
[0048] from Figure 1 It can be seen that the diffraction peaks of each ceramic sample after high entropy treatment are consistent with the standard pdf card (PDF#27-0052), and the standard pdf card corresponds to the δ-Bi2O3 phase, indicating that the high entropy treatment can stabilize the high conductivity δ-Bi2O3 phase at room temperature;
[0049] from Figure 2 It can be seen that after annealing at 500℃ for 100h, the diffraction peaks of each sample are still consistent with the standard PDF card (PDF#27-0052), indicating that the high entropy treatment can make the high conductivity δ-Bi2O3 phase stable in a medium and low temperature (500℃) long-term working environment;
[0050] from Figure 3 It can be seen that the elements of high-entropy ceramic samples doped with different proportions are evenly distributed without obvious element segregation;
[0051] from Figure 4It can be seen that in the temperature range of 200-600℃, the comparison of CeO2-based, yttria-stabilized zirconia ceramics and single-doped (Er 0.2 Bi 0.8 )2O3 ceramics, the high entropy ceramics prepared by the present invention have a higher conductivity than the three, and ((Er 0.2 Dy 0.2 G 0.2 Zr 0.2 Y 0.2 ) 0.2 Bi 0.8 )2O3 high entropy ceramics at medium and low temperature points (400, 500, 600℃) compared with single doping (Er 0.2 Bi 0.8 )2O3 ceramics, the electrical conductivity is improved by nearly 1 order of magnitude.
[0052] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A solid electrolyte high entropy ceramic with high electrical conductivity, characterized in that: The structure of the solid electrolyte high entropy ceramic is as follows: (On 0.2 Of 0.2 Gd 0.2 Zr 0.2 THE 0.2 ) x Bi 1-x )2O3, Where x=0.1~0.
2.
2. The solid electrolyte high entropy ceramic with high conductivity according to claim 1, characterized in that: The solid electrolyte high entropy ceramic has a cubic fluorite crystal structure and is composed of irregular polygonal grains.
3. The method for preparing a solid electrolyte high entropy ceramic with high conductivity according to claim 1 or 2, characterized in that: The following steps are involved: (1) Weighing Er2O3 powder, Dy2O3 powder, Gd2O3 powder, ZrO2 powder, Y2O3 powder and Bi2O3 powder in stoichiometric ratios respectively, and then ball-milling the weighed oxide powders to obtain a mixed powder; (2) calcining the mixed powder in a muffle furnace, and grinding and sieving the mixed powder after calcination to obtain a precursor powder; (3) Pressing the precursor powder into a disc, placing the disc in a crucible, laying the precursor powder on the bottom of the crucible, and then sintering the crucible in a muffle furnace to obtain a solid electrolyte high entropy ceramic.
4. The method for preparing a solid electrolyte high entropy ceramic with high conductivity according to claim 3, characterized in that: The ball milling media in step (1) are zirconium oxide grinding balls and anhydrous ethanol, wherein the mass ratio of the raw material powder to the zirconium oxide grinding balls and anhydrous ethanol is 1:(5-6):(5-6), the ball mill speed is 300-350 rpm, and the ball milling time is 20-24 hours.
5. The method for preparing a solid electrolyte high entropy ceramic with high conductivity according to claim 3, characterized in that: The muffle furnace calcination temperature in step (2) is 500-600° C., and the calcination time is 5-6 hours.
6. The method for preparing a solid electrolyte high entropy ceramic with high conductivity according to claim 1, characterized in that: In step (3), the sintering temperature of the muffle furnace is 800-950° C., and the insulation time is 8-10 hours.
Citation Information
Patent Citations
Composite solid electrolyte and preparation method thereof
CN112271313A
High-entropy metal sulfur phosphide electrolyte material and preparation method thereof
CN115312838A
A-bit and B-bit common high-entropy perovskite type high-entropy ceramic material as well as preparation method and application of A-bit and B-bit common high-entropy perovskite type high-entropy ceramic material
CN117049875A
High-energy-storage sodium niobate-based high-entropy ceramic material as well as preparation method and application thereof
CN117819964A
Method for preparing high-entropy ceramic based on flash burning variable current and high-entropy ceramic
CN118405919A